A new species of Leporinus (Characiformes: Anostomidae) from the rio Jequitinhonha, eastern Brazil - Birindelli, José Luís Olivan; Vieira, Fábio; Garavello, Júlio César (Zootaxa, 2026)
A new species of Leporinus (Characiformes: Anostomidae) is described from tributaries of the upper rio Jequitinhonha basin, eastern Brazil, based on morphological and molecular evidence. The new species is distinguished from congeners by the unique combination of three premaxillary and four dentary teeth, 12 scale rows around the caudal peduncle, three large dark midlateral blotches on the body, and a conspicuous red spot on the posterior portion of the upper lip. It is further characterized by its reduced body size, with the largest known specimen reaching only 128.6 mm of standard length, an uncommon condition among anostomids. DNA barcoding analyses (COI) revealed genetic divergences ranging from 3.8% to 8.5% from its closest congeners (L. microphthalmus and L. amblyrhynchus) and consistently recovered all specimens of the new species as a distinct Molecular Operational Taxonomic Unit. Phylogenetic analyses placed the new species within the L. melanopleura clade, together with L. amblyrhynchus, L. melanopleura, L. melanopleurodes, and L. microphthalmus. The species is endemic to a restricted area of the rio Jequitinhonha basin, where its populations are likely severely fragmented and threatened by multiple anthropogenic impacts. The discovery of this small-sized anostomid adds to the growing evidence of high levels of endemism and conservation concerns in eastern Brazilian coastal drainages.